The Formation of a Polycentric City in Transitional China in a Three-Level Analysis Framework: The Case Study of Hangzhou - Liang Zhang; Xianfan Shu; Jiaojiao Luo (Land, 2022)
Given cities’ different development backgrounds, the spatial evolution of each city has a path-dependent development track. Understanding the characteristics of urban spatial structure evolution in contemporary China is essential for sustainable urban development. By establishing a theoretical framework comprising a macro-background, planning tool, and resource allocation, this paper takes Hangzhou as an example to analyze the evolutionary process of the polycentric spatial structure and reveal the formation characteristics of its polycentric urban spatial form. The results show that (1) its institutional background and planning tools are the driving forces behind the formation of the polycentric structure in Hangzhou, i.e., the evolution of the polycentric structure mainly relies on planning guidance and government forces rather than being market-driven. (2) Under the government-led mode of polycentric formation, urban elements, such as education, medical care, transportation, and green space, are still concentrated in the main urban center, while subcenters lack the necessary public facilities and are underdeveloped. (3) The spatial distribution of the population and nightlights also shows the trend of diminishing concentric circles with the main center at the core. Therefore, it is impossible to implement polycentric cities by decentralizing the population and industries alone. The comprehensive consideration of capital investment, production services, and the supply of life service facilities is also required. This empirical study can complement empirical evidence in order to verify the validity of polycentrism as a potential solution that can alleviate the sprawl of central urban areas.